Utilization of MSW-Derived Biochar for Production of Iron Through Solid–Solid Reaction - Hadi Purwanto; Alya Naili Rozhan; Danial Faiz Zulani; Mohd Hanafi Ani (International Islamic University Malaysia Engineering Journal)
Every year, the increasing human population has contributed to the abundance of Municipal Solid Waste (MSW) at designated landfills, especially in Malaysia. On the other hand, in the iron and steel industry, a high demand for steel production has caused an increase in CO2 production, which would, unfortunately, contribute to global warming. Therefore, sustainable solutions are needed to avoid this environmental crisis from worsening. This study employed an effective approach, utilizing low-grade iron ore from Pahang to produce iron by using MSW-derived biochar as an alternative to coal as a reductant and energy source. This project aims to study the mechanism of the solid-solid reduction reaction of iron ore with carbon. MSW was collected and prepared before the slow pyrolysis to obtain the MSW-derived biochar. Iron ore was characterized by using X-Ray Fluorescence (XRF) for elemental composition determination and X-Ray Diffraction (XRD) to observe the presence of mineral phases. In this research, the solid-solid reaction was conducted for the reduction reaction at 900? with residence times of 1 hour, 3 hours, and 5 hours. From the research that has been conducted, temperature and residence time were found to influence the elemental composition, reduction degree, and mineral phase transformation of iron.